A qualitative study of factors influencing retention of doctors and nurses at rural healthcare facilities in Bangladesh - Kwame Darkwa, Emmanuel; Sophia Newman, M.; Kawkab, Mahmud; Elahi Chowdhury, Mahbub (© 2015 BioMed Central Ltd., 2016)
This article was published in BMC Health Services Research [© 2015 BioMed Central Ltd.] and the definite version is available at: http://bmchealthservres.biomedcentral.com/articles/10.1186/s12913-015-1012-z